Measurement properties of the Rajka–Langeland severity score in children and adults with atopic dermatitis. (13th July 2020) - Silverberg, J.I.; Lei, D.; Yousaf, M.; Janmohamed, S.R.; Vakharia, P.P.; Chopra, R.; Chavda, R.; Gabriel, S.; Patel, K.R.; Singam, V.; Kantor, R.; Hsu, Derek Y.
Summary: Background: Multiple atopic dermatitis (AD) severity scales exist, with no gold standard for use in clinical practice. Objectives: To determine the measurement properties of the Rajka–Langeland score and compare it with other clinician‐reported outcomes in adults and children with AD. Methods: We performed a prospective dermatology practice‐based study using questionnaires and evaluation by a dermatologist ( n = 427). Results: Rajka–Langeland had good concurrent validity with the Eczema Area and Severity Index (Spearman rho = 0·63), SCORing AD (SCORAD) (rho = 0·61), objective‐SCORAD (rho = 0·52) and body surface area (rho = 0·51); good convergent validity with the numeric rating scale average‐itch (rho = 0·60) and worst‐itch (rho = 0·59), Patient‐Oriented Eczema Measure (rho = 0·57), Dermatology Life Quality Index (rho = 0·53), Patient‐Reported Outcomes Measurement Information System Itch Questionnaire (rho = 0·35–0·55) in adults and/or children; fair discriminant validity for patient‐ and physician‐reported global AD severity; good responsiveness to change of severity of AD and itch; good reliability; internal consistency; with no floor or ceiling effects. Interpretability bands (3, clear/almost clear; 4–5, mild; 6–7, moderate; 8–9, severe) and minimal clinically important difference (1 point) were established. Conclusions: The Rajka–Langeland score showed good construct validity, reliability, internal consistency and responsiveness in adults and children with AD. Abstract : What is already known about this topic? The Rajka–Langeland score was developed to assess the severity of atopic dermatitis (AD). Limited results have been demonstrated about its validity, responsiveness and interpretability. What does this study add? This study demonstrated that the Rajka–Langeland score has good construct validity, responsiveness, reliability and interpretability in the assessment of AD in adults and children. The Rajka–Langeland score has sufficient validity, reliability and feasibility to be used as an assessment of AD severity in adults and children in clinical practice and trials. What are the clinical implications of the work? Clinicians should consider using Rajka–Langeland scoring to assess AD severity and guide therapeutic decision making in clinical practice. Linked Comment: Reich. Br J Dermatol 2021; 184:6–7 . Plain language summary available online